Back to the past: the historical roots of labour-saving automation - Jacopo Staccioli; Maria Enrica Virgillito (Global Labor Organization (GLO), 2020)
This paper, relying on a still relatively unexplored long-term dataset on U.S. patenting activity, provides empirical evidence on the history of labour-saving innovations back to early 19th century. The identification of mechanisation/automation heuristics, retrieved via textual content analysis on current robotic technologies by Montobbio et al. (2020), allows to focus on a limited set of CPC codes where mechanisation and automation technologies are more prevalent. We track their time evolution, clustering, eventual emergence of wavy behaviour, and their comovements with long-term GDP growth. Our results challenge both the general-purpose technology approach and the strict 50-year Kondratiev cycle, while provide evidence of the emergence of erratic constellations of heterogeneous technological artefacts, in line with the developmentblock approach enabled by autocatalytic systems.
Keywords: O3; C38; J24; 330; Labour-Saving Technologies; Search Heuristics; Industrial Revolutions; Wavelet analysis